2010
DOI: 10.1159/000316613
|View full text |Cite
|
Sign up to set email alerts
|

Nonmotor Disturbances in Parkinson’s Disease

Claudio L. Bassetti

Abstract: Nonmotor disturbances (NMDs) affect most patients with Parkinson’s disease (PD) and often have a profound impact on their quality of life. NMDs such as depression, anxiety, fatigue, REM sleep behavior disorder, constipation, delayed gastric emptying, altered olfaction and pain can precede the onset of motor symptoms. Other NMDs, including hallucinations, dementia, excessive daytime sleepiness, insomnia, orthostatic hypotension and bladder disturbances, typically appear later in the course of PD. For most NMDs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 247 publications
0
24
0
2
Order By: Relevance
“…Orthostatic hypotension or postural hypotension is another common non-motor symptom. The prevalence is between 20 and 50% [42,43]. Orthostatic hypotension has been previously reported to be associated with falls in persons with PD [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Orthostatic hypotension or postural hypotension is another common non-motor symptom. The prevalence is between 20 and 50% [42,43]. Orthostatic hypotension has been previously reported to be associated with falls in persons with PD [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an estimated proportion of 90 % of PD patients exhibit olfactory deficits [8991]. Several studies detected olfactory deficits early in the course of the disease, before the appearance of motor symptoms (for review, see [92]).…”
Section: Spread Of Synucleinopathy and Progression Of Parkinson’s Dismentioning
confidence: 99%
“…Several of these NMS were described in James Parkinson’s original essay. They can include sleep disturbances, neuropsychiatric and cognitive deficits, and autonomic and sensory dysfunction (Bassetti, 2011; Chaudhuri et al, 2011). Further highlighting their importance, retrospective studies showed that some NMS, can appear several years before the onset of the classical motor signs (Abbott et al, 2005, 2007; Ross et al, 2006).…”
Section: An Updated View Of An Old Mystery: the Non-motor Symptoms Ofmentioning
confidence: 99%